Exploring the molecular mechanism of Gan Shuang granules for the treatment of non-alcoholic steatohepatitis using network pharmacology, molecular docking, and experimental verification - Zhi, Guoguo; Shao, Bingjie; Zheng, Tianyan; Mu, Jie; Li, Jingwei; Feng, Yiyuan; Zhu, Sha; Dang, Yanni; Liu, Feng; Wang, Dong (Frontiers in Pharmacology, 2023)
ABSTRACT Background. With the gradual increase in prevalence in recent years, nonalcoholic steatohepatitis (NASH) has become one of the major health problems that urgently need to be addressed worldwide. GanShuang Granules (GSG) are derived from the classical Chinese formula Xiaoyao San and are mainly used in the clinical treatment of chronic liver diseases. Objective. To identify the core components, key targets and potential pharmacological mechanisms of GSG for the treatment of NAFLD using network-based pharmacology combined with molecular docking prediction and in vivo experimental validation. Methods. First, GSG components were identified with the help of UHPLC-Q/Orbitrap-MS/MS. Then, the targets corresponding to GSG components were collected from public databases, along with disease genes for NAFLD. The core targets and molecular mechanisms of GSG for NAFLD treatment were predicted by protein‒protein interaction (PPI) network, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses. Molecular docking of the core target-component interactions was simulated using AutoDock Vina software. Finally, in vivo experiments were carried out for further validations. Results. Combining UHPLC-Q/Orbitrap-MS/MS data analysis and public database data, a total of 346 cross-targets were obtained, corresponding to 81 components. The subnetwork with an MCODE score of 53.623 is a potential core target group for this study. GO and KEGG enrichment analyses showed that the targets of GSG in NAFLD were mostly related to oxidative stress, the NF-κB signaling pathway and the apoptosis signaling pathway. By integrating the results of network pharmacology analysis, the core objectives of this study mainly include AKT1, CASP9, TNF and CASP8. The core ingredients are related to resveratrol and non-septine. The molecular docking results showed that fisetin bound best to AKT1. In addition, in vivo experiments showed that GSG have medicinal effects that include improving abnormal liver lipid accumulation and anti-inflammation and reducing liver injury during the treatment of NAFLD/NASH. The molecular mechanisms involved are mainly reflected in the inhibitory effects on the NF-κB/IκB signaling pathway and its downstream inflammation and apoptosis signals. Conclusion. The therapeutic effect of GSG on NAFLD/NASH reflects the unique advantages of multi-component, multi-target and multi-pathway Chinese medicine treatment.